Comparativo de productividad de tres variedades de pepino (cucumis sativus l.) en el Alto Mayo - Garcia Córdova, Nild (2012)
This research paper entitled "Comparative productivity of three varieties of cucumber (Cucumis sativus L.) in the Alto Mayo," aimed to: evaluate the performance of three varieties of cucumber (Cucumis sativus L.) in the Upper May , determine the most promising variety for the Alto Mayo and perform economic analysis of the treatments under study. The research was conducted in the fields of the farm "San Juan" Orchids Waqanki, owned by Mr. Francisco Altamirano Sanchez district, province of Moyobamba. Located in Hot Springs Road Km 4-Moyobamba, with the location coordinates of the experimental field: 18 M 0281586, UTM 9328202, Height: 962 msnmm. 3 treatments were evaluated: T1 (regional ecotype), T2 (Marketmore 76) and T3 (Hybrid Stonewall) for which we used a design of completely randomized blocks with five replications. The major conclusions were: T3 (hybrid Stonewall), obtained better results in the different variables evaluated as plant length, number of leaves per plant, number of fruits per plant, number of harvested fruits, treatments T2 (76 Marketmore ) and T3 (Hybrid Stonewall) obtained similar values in fruit weight, fruit length and diameter of fruits and All treatments yielded rates of B / C greater than 1. Since the T1 (regional ecotype) yielded a value of 1.22, T2 (Marketmore 76) a higher value of 2.74 and T3 (Hybrid Stonewall) the highest value with 5.89 and a net profit of S /. 97,459.76 soles.